The association between oxidative balance score and sleep duration: a mediation analysis of a cross-sectional study - Hao, Guihua; Zhao, Xiaomei; Fu, Weiwei; Wu, Yiwen; Dai, Jingjing; Qian, Yifeng; Xie, Tian; Hou, Lili; Shi, Wentao (Frontiers in Nutrition, 2024)
The Oxidative Balance Score (OBS), which reflects overall oxidation through diet and lifestyle, has been linked to sleep, but few studies have clarified this relationship. We investigated the association between OBS and sleep duration, and whether oxidative stress (OS) and inflammation mediate the underlying mechanisms.: Data were obtained from the National Health and Nutrition Examination Survey spanning the years 2007 to 2018. Multivariable logistic regression analyses were used to evaluate the association between OBS and the risk of sleep duration. Mediation analyses were conducted to investigate the role of OS and inflammatory markers.Results: A significant negative association was found between OBS and sleep duration (P<0.01). Meanwhile, compared to participants in OBS tertile 1, the ORs (95% CIs) of incident short sleep duration were 0.78 (0.72-0.86) and 0.72 (0.67-0.79) (both P<0.01) for OBS tertile 2 and 3, respectively. And the ORs (95% CIs) of incident long sleep duration were 0.83 (0.73, 0.95) and 0.66 (0.57, 0.75) (both P<0.01) for OBS tertiles 2 and 3 after adjustment for multivariate variables. A linear relationship between OBS and short/long sleep duration (P for non-linearity = 0.69/0.94, both P<0.01) were revealed. Mediation analysis showed absolute neutrophil count, serum total bilirubin mediated the association between OBS and short/long sleep duration with 5.72%, 13.41% proportion of mediation, respectively (both P < 0.001).Conclusions: OBS is negatively associated with sleep duration. OS and inflammatory biomarkers mediate the relationship.